Pengaruh Perputaran Modal Kerja, Perputaran Kas, Perputaran Piutang, Dan Perputaran Persediaan Terhadap Profitabilitas : Studi Empiris Pada Perusahaan Pertambangan Periode 2020-2024 - Istiqomah Istiqomah; Indah Rahayu Lestari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Profitability is one of the most important indicators for assessing a company's financial performance, as reflects the extent to which management efficiently manages resources to generate profits for the company. The purpose of this study was to determine the effect of working capital turnover, cash turnover, accounts receivable turnover, and inventory turnover on the profitability of mining companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The sample was selected using a purposive sampling technique with a non-probabilistic sampling approach based on specific criteria. As a result, 36 companies qualified for this study. Data were processed using multiple linear regression analysis with SPSS version 25. The results of this study indicate that working capital turnover has a positive effect on profitability, while cash turnover has no significant effect. Meanwhile, receivable turnover has a positive effect on profitability, and inventory turnover has a negative effect on profitability. These results indicate that effective current asset management in company can increase profits, while the low contribution of cash turnover indicates that liquidity don”t always correlate with profitability, the negative impact of inventory turnover indicates the potential for decreased profits if inventory management is suboptimal.. This study confirms that working capital management has diverse impact on profitability. Working capital and accounts receivable turnover are driving factors for improved financial performance, while cash turnover does not directly impact profits, inventory turnover can negatively impact profitability if not managed effectively.